Author Correction: Isolated Rh atoms in dehydrogenation catalysis (Scientific Reports, (2023), 13, 1, (4458), 10.1038/s41598-023-31157-y) - Wittkämper, Haiko; Hock, Rainer; Weißer, Matthias; Dallmann, Johannes; Vogel, Carola; Raman, Narayanan; Taccardi, Nicola; Haumann, Marco; Wasserscheid, Peter; Hsieh, Tzung En; Maisel, Sven; Moritz, Michael; et al. (Scientific Reports, 2023)
Correction to: Scientific Reports, published online 17 March 2023 The original version of this Article contained an error in the spelling of the author Nicola Taccardi, which was incorrectly given as Nicola Tacardi. The original Article has been corrected.
CRIS-Team Scopus Importer:2023-06-30

Highly Effective Propane Dehydrogenation Using Ga-Rh Supported Catalytically Active Liquid Metal Solutions - Raman, Narayanan; Maisel, Sven; Grabau, Mathias; Taccardi, Nicola; Debuschewitz, Jonas; Wolf, Moritz; Wittkämper, Haiko; Bauer, Tanja; Wu, Mingjian; Haumann, Marco; Papp, Christian; Görling, Andreas; et al. (ACS Catalysis, 2019)
Our contribution demonstrates that rhodium, an element that has barely been reported as an active metal for selective dehydrogenation of alkanes becomes a very active, selective, and robust dehydrogenation catalyst when exposed to propane in the form of single atoms at the interface of a solid-supported, highly dynamic liquid Ga-Rh mixture. We demonstrate that the transition to a fully liquid supported alloy droplet at Ga/Rh ratios above 80, results in a drastic increase in catalyst activity with high propylene selectivity. The combining results from catalytic studies, X-ray photoelectron spectroscopy, IR-spectroscopy under reaction conditions, microscopy, and density-functional theory calculations, we obtained a comprehensive microscopy picture of the working principle of the Ga-Rh supported catalytically active liquid metal solution.
CRIS-Team Scopus Importer:2019-10-18
Keywords: alkane; alkene; catalysis; dehydrogenation; gallium; rhodium

Isolated Rh atoms in dehydrogenation catalysis - Wittkämper, Haiko; Hock, Rainer; Weißer, Matthias; Dallmann, Johannes; Vogel, Carola; Raman, Narayanan; Tacardi, Nicola; Haumann, Marco; Wasserscheid, Peter; Hsieh, Tzung En; Maisel, Sven; Moritz, Michael; et al. (Scientific Reports, 2023)
Isolated active sites have great potential to be highly efficient and stable in heterogeneous catalysis, while enabling low costs due to the low transition metal content. Herein, we present results on the synthesis, first catalytic trials, and characterization of the Ga9Rh2 phase and the hitherto not-studied Ga3Rh phase. We used XRD and TEM for structural characterization, and with XPS, EDX we accessed the chemical composition and electronic structure of the intermetallic compounds. In combination with catalytic tests of these phases in the challenging propane dehydrogenation and by DFT calculations, we obtain a comprehensive picture of these novel catalyst materials. Their specific crystallographic structure leads to isolated Rhodium sites, which is proposed to be the decisive factor for the catalytic properties of the systems.
CRIS-Team Scopus Importer:2023-03-31

Key Parameters for the Synthesis of Active and Selective Nanostructured 3d Metal Catalysts Starting from Coordination Compounds - Case Study: Nickel Mediated Reductive Amination - Klarner, Mara; Blach, Patricia; Wittkämper, Haiko; De Jonge, Niels; Papp, Christian; Kempe, Rhett (ChemCatChem, 2021)
The design of nanostructured catalysts based on earth-abundant metals that mediate important reactions efficiently, selectively and with a broad scope is highly desirable. Unfortunately, the synthesis of such catalysts is poorly understood. We report here on highly active Ni catalysts for the reductive amination of ketones by ammonia employing hydrogen as a reducing agent. The key functions of the Ni-salen precursor complex during catalyst synthesis have been identified: (1) Ni-salen complexes sublime during catalyst synthesis, which allows molecular dispersion of the metal precursor on the support material. (2) The salen ligand forms a nitrogen-doped carbon shell by decomposition, which embeds and stabilizes the Ni nanoparticles on the gamma-Al2O3 support. (3) Parameters, such as flow rate of the pyrolysis gas, determine the carbon supply for the embedding process of Ni nanoparticles.
CRIS-Team WoS Importer:2021-06-11

Lattice Opening upon Bulk Reductive Covalent Functionalization of Black Phosphorus - Wild, Stefan; Fickert, Michael; Mitrovic, Aleksandra; Lloret Segura, Vicente Josep; Neiß, Christian; Alejandro Vidal-Moya, Jose; Angel Rivero-Crespo, Miguel; Leyva-Perez, Antonio; Werbach, Katharina; Peterlik, Herwig; Grabau, Mathias; Wittkämper, Haiko; et al. (Angewandte Chemie International Edition, 2019)

Oxidation induced restructuring of Rh-Ga SCALMS model catalyst systems - Wittkämper, Haiko; Maisel, Sven; Wu, Mingjian; Frisch, Johannes; Wilks, Regan G.; Grabau, Mathias; Spiecker, Erdmann; Bär, Marcus; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (Journal of Chemical Physics, 2020)
Supported catalytically active liquid metal solutions have been receiving increasing attention recently. We investigated the oxidation behavior of macroscopic Rh-Ga alloy droplets and Rh-Ga model catalyst nanoparticles supported on SiO2/Si(100) with low Rh content (<2.5 at. %) by x-ray photoelectron spectroscopy in ultra-high vacuum and under near-ambient pressure conditions using different photon energies and also using transmission electron microscopy. The experiments are accompanied by computational studies on the Ga oxide/Rh-Ga interface and Rh-Ga intermetallic compounds. For both Rh-Ga alloy droplets and Rh-Ga model catalyst nanoparticles, exposure to molecular oxygen leads to the formation of an oxide shell in which Rh is enriched. Transmission electron microscopy on the Rh-Ga nanoparticles confirms the formation of an ∼4 nm thick gallium oxide film containing Rh. Based on ab initio molecular dynamics and computational studies on the Ga2O3/Ga interface, it is concluded that Rh incorporation into the Ga2O3 film occurs by substituting octahedrally coordinated Ga.
CRIS-Team Scopus Importer:2020-09-25

Poisoning Resistance of Liquid GaPt Supported Catalytically Active Liquid Metal Solutions Model Systems - Wichmann, Christoph; Moritz, Michael; Wittkämper, Haiko; Hsieh, Tzung En; Frisch, Johannes; Bär, Marcus; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2024)
SiOx-supported liquid GaPt systems show remarkable catalytic activity and stability in lab-scale alkane dehydrogenation reactions. However, large-scale applications provide additional challenges, like the presence of catalyst poisons in the catalytic feed that strongly bind and block active sites. A common poison are sulfur traces, which tend to interact strongly with transition metals like Pt. Therefore, macroscopic GaPt alloy droplets with low Pt content (1 at. %) and nanoscopic GaPt particles were investigated during the exposure to thiophene as catalyst poison and organic sulfur source. The measurements were performed using X-ray photoelectron spectroscopy under ultrahigh vacuum and near-ambient pressure conditions. We observed the formation of a ∼2.5 nm Ga sulfide layer, in which Pt accumulates. Notably, we do not find the formation of Pt sulfides in the model systems. For higher temperatures (>650 K), the formed Ga sulfides dissolve into the liquid metallic Ga-matrix, resulting in a Ga sulfide-free gas/liquid interface. In reference measurements, it was shown that the pure Pt particles are poisoned by sulfur and Ga is not reactive toward the formation of sulfides. Pt seems to play a key role in the formation of Ga sulfides since particles only consisting of Ga show only minor sulfur deposits.
CRIS-Team Scopus Importer:2024-06-07

Poly(benzimidazobenzophenanthroline)-Ladder-Type Two-Dimensional Conjugated Covalent Organic Framework for Fast Proton Storage** - Wang, Mingchao; Wang, Gang; Naisa, Chandrasekhar; Fu, Yubin; Gali, Sai Manoj; Paasch, Silvia; Wang, Mao; Wittkämper, Haiko; Papp, Christian; Brunner, Eike; Zhou, Shengqiang; Beljonne, David; et al. (Angewandte Chemie International Edition, 2023)
Electrochemical proton storage plays an essential role in designing next-generation high-rate energy storage devices, e.g., aqueous batteries. Two-dimensional conjugated covalent organic frameworks (2D c-COFs) are promising electrode materials, but their competitive proton and metal-ion insertion mechanisms remain elusive, and proton storage in COFs is rarely explored. Here, we report a perinone-based poly(benzimidazobenzophenanthroline) (BBL)-ladder-type 2D c-COF for fast proton storage in both a mild aqueous Zn-ion electrolyte and strong acid. We unveil that the discharged C−O− groups exhibit largely reduced basicity due to the considerable π-delocalization in perinone, thus affording the 2D c-COF a unique affinity for protons with fast kinetics. As a consequence, the 2D c-COF electrode presents an outstanding rate capability of up to 200 A g−1 (over 2500 C), surpassing the state-of-the-art conjugated polymers, COFs, and metal–organic frameworks. Our work reports the first example of pure proton storage among COFs and highlights the great potential of BBL-ladder-type 2D conjugated polymers in future energy devices.
CRIS-Team Scopus Importer:2023-10-20
Keywords: 2D Conjugated COFs; Poly(Benzimidazobenzophenanthroline); Proton Storage; Strong Acid; Zn-Ion Electrolyte

Pt-Ga Model SCALMS on Modified HOPG: Thermal Behavior and Stability in UHV and under Near-Ambient Conditions - Hohner, Chantal; Kettner, Miroslav; Stumm, Corinna; Blaumeiser, Dominik; Wittkämper, Haiko; Grabau, Mathias; Schwarz, Matthias; Schuschke, Christian; Lykhach, Yaroslava; Papp, Christian; Steinrück, Hans-Peter; Libuda, Jörg (Journal of Physical Chemistry C, 2020)
We have prepared model systems for Pt-Ga supported catalytically active liquid metal solutions (SCALMS) by physical vapor deposition of Pt and Ga onto highly oriented pyrolytic graphite (HOPG). Prior to metal deposition, the HOPG support was modified by Ar+ bombardment. In this work, we focus on the stability of the Pt-Ga deposits toward agglomeration, which is a critical challenge in application. Specifically, we study the behavior of the model catalysts in ultrahigh vacuum (UHV) and under near ambient pressure (NAP) conditions at different temperatures. We use CO as a probe molecule to examine changes in the surface composition of the Pt-Ga deposits by in situ infrared reflection absorption spectroscopy (IRAS). In specific, we combine IRAS and ex situ atomic force microscopy (AFM) to study changes induced by annealing. We find that sintering effects are strongly dependent on the thickness of the deposited Pt-Ga layers. Our data suggest that particle ripening leads to a separation of the system into disperse Pt-rich and large Ga-rich particles. In the NAP regime, we performed simultaneous measurements with polarization modulation IRAS (PM-IRAS) and near ambient pressure X-ray photoelectron spectroscopy (NAP-XPS). The alloying of Pt and Ga is accompanied by a shift of Pt 4f and Ga 3d photoelectron lines to higher binding energies. Although partial oxidation of Ga is observed upon CO exposure at pressures in the millibar regime, PM-IRAS shows'adsorbed CO at a frequency typical for Pt ensembles in a Ga matrix.
CRIS-Team WoS Importer:2020-02-18

Supported Catalytically Active Liquid Metal Solutions: Liquid Metal Catalysis with Ternary Alloys, Enhancing Activity in Propane Dehydrogenation - Moritz, Michael; Maisel, Sven; Raman, Narayanan; Wittkämper, Haiko; Wichmann, Christoph; Grabau, Mathias; Kahraman, Deniz; Steffen, Julien; Taccardi, Nicola; Görling, Andreas; Haumann, Marco; Wasserscheid, Peter; et al. (ACS Catalysis, 2024)
The research and optimization of catalysts are instrumental in revolutionizing chemical processes and making them viable in terms of energy and resources. Supported catalytically active liquid metal solutions (SCALMS) are highly active and stable in the harsh environment of the dehydrogenation reaction of alkanes. This is attributed to their liquid and dynamic nature and their isolated catalytically active single-atom sites. SCALMS consists of a liquid metal matrix (gallium) in which a catalytically active transition metal (platinum, rhodium, palladium, or nickel) is dissolved. Binary SCALMS systems are the subject of extensive research, aiming at a better understanding for achieving optimal performance. This work uses a combined multidisciplinary approach to examine ternary systems of the active transition metal platinum with mixtures of gallium with either tin or indium. Reaction engineering and surface chemical analysis by X-ray photoelectron spectroscopy are combined with density functional theory (DFT) and machine learning force field (ML-FF) simulations. Introducing a third metal into the mixture alters the reactivity, surface composition, and concentration gradient in the liquid metal catalyst. We demonstrate that changes in catalytic reactivity correlate with changes in the surface concentration of the active transition metal platinum and of the position of the d-band center. These findings hold great promise for future research directions as they offer potential starting points for developing SCALMS systems.
CRIS-Team Scopus Importer:2024-04-19
Keywords: AIMD; dehydrogenation; DFT; ML-FF; single-atom catalysis; XPS

Surface oxidation-induced restructuring of liquid Pd-Ga SCALMS model catalysts - Wittkämper, Haiko; Maisel, Sven; Moritz, Michael; Grabau, Mathias; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (Physical Chemistry Chemical Physics, 2021)
We have examined model systems for the recently reported Pd-Ga Supported Catalytically Active Liquid Metal Solutions (SCALMS) catalysts using near-ambient pressure X-ray photoelectron spectroscopy (NAP-XPS) under oxidizing conditions. Gallium is known to be highly prone to oxidation and in practical applications, handling of the catalyst material in air or the presence of traces of oxygen in the reactor are unavoidable. Therefore, we expect our results to be of high relevance for the application of Ga-based SCALMS catalysts. Pd-Ga alloy samples of 1.3 and 1.8 at% Pd content were exposed to molecular oxygen at different pressures between 3 x 10(-7) and 1 mbar and a temperature of 550 K. We observe the formation of wetting Ga2O3 films upon exposure to molecular oxygen. The absolute thicknesses of the oxide films depend on oxygen pressure, with values ranging from similar to 12 angstrom at 10(-7) to 10(-5) mbar to similar to 50 angstrom at 1 mbar. The formed metal-oxide interface leads to a redistribution of Pd, which accumulates at the boundary between the wetting oxide film and the metal substrate as a response to the oxide film growth. A maximum Pd 3d intensity is observed at an oxide thickness of 5 angstrom. For thicker films, the Pd 3d signal and the Ga 3d signal ascribed to the metallic substrate decrease in parallel, which is attributed to the oxide layer growing on top of the liquid metal alloy. From this observation, we conclude that no significant amount of Pd is bound in the newly formed oxide film. Density-functional theory (DFT) calculations support the experimental observations.
CRIS-Team WoS Importer:2021-08-06

Temperature-dependent dielectric anomalies in powder aerosol deposited ferroelectric ceramic films - Eckstein, Udo; Exner, Jörg; Bencan Golob, Andreja; Ziberna, Katarina; Drazic, Goran; Ursic, Hana; Wittkämper, Haiko; Papp, Christian; Kita, Jaroslaw; Moos, Ralf; Webber, Kyle Grant; Khansur, Neamul Hayet (Journal of Materiomics, 2022)
Room-temperature fabrication of functional ceramic films using powder aerosol deposition (AD) is important for practical applications. However, the as-processed ferroelectric films show unusual temperature-dependent dielectric response, including enhanced conductivity in the as-processed state and subsequent significant increase in the permittivity following heat treatment. In this work, we investigate the influence of the residual internal stresses developed during the high-impact consolidation process on the dielectric response. Moreover, the recombination of charged defects generated during deposition is driven by the temperature and the atmospheric condition during the heat treatment as well as the carrier gas type used during deposition. Thermal treatment up to 500 °C in different atmospheres was used to tune the dielectric and ferroelectric response, highlighting that irrespective of the type of carrier gas, AD deposition process induces charged defects in polar oxide ceramics that can be reduced through heat-treatment far-below their bulk sintering temperature. Macroscopic electromechanical properties are contrasted to in-situ heating scanning transmission electron microscopy to observe possible local effects, such as crystallization, grain growth, crystal defect structure, or grain reorientation. In addition X-ray diffraction and X-ray photoelectron spectroscopy studies were conducted to gain insight into the effect of annealing on the crystal structure and local moisture adsorption.
CRIS-Team Scopus Importer:2022-11-18
Keywords: Aerosol deposition; Energy storage; Functional ceramic thick films; Structural characterization

Temperature-dependent XPS studies on Ga-In alloys through the melting-point - Wittkämper, Haiko; Maisel, Sven; Moritz, Michael; Grabau, Mathias; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (Surface Science, 2022)
Gallium indium alloys are known to be liquid at remarkably low temperatures. Herein, we provide X-ray photoelectron spectroscopy (XPS) studies and DFT-based ab-initio molecular dynamics (MD) calculations on the composition of the liquid alloy surface. We find that alloying Ga and In in ratios close to the eutectic composition results in only minor signal shifts of the corresponding In core levels. The topmost surface layer of the liquid alloy exhibits significant In enrichment for all measured temperatures, between 300 K to 800 K the observed enrichment slightly decreases with increasing temperature. This behavior is seen in both temperature-dependent XPS and ab-initio MD simulations. Furthermore, we investigate changes in the surface composition during the liquid-to-solid phase transition by time-dependent XPS during cooling of the alloy sample. The surface of the alloy presents an advantageous nucleation site, where we regularly observe the precipitation of indium. During cooling, the precipitation processes were followed by both XPS and by monitoring the sample temperature/heating power.
CRIS-Team Scopus Importer:2022-04-14
Keywords: DFT; GaIn; XPS

Unraveling the Effect of Rh Isolation on Shallow d States of Gallium-Rhodium Alloys - Hsieh, Tzung En; Maisel, Sven; Wittkämper, Haiko; Frisch, Johannes; Steffen, Julien; Wilks, Regan G.; Papp, Christian; Görling, Andreas; Bär, Marcus (Journal of Physical Chemistry C, 2023)
In this study, we report the electronic and chemical structure of supported GaRh alloys as model systems for the active phase in supported catalytically active liquid metal solutions (SCALMS). We prepared a series of gallium-rhodium samples with different Rh contents and tracked the evolution of the sample topography and surface electronic structure via photoemission spectroscopy in combination with ab initio calculations and electron microscopy. Our results reveal a characteristic shift of the Rh 3d core levels and narrowing and shifting of the Rh 4d derived band with decreasing Rh content. Calculations show that these spectroscopic observations can be explained by the coexistence of isolated Rh atoms in random GaRh alloys and GaRh intermetallic compounds (IMCs). These results contribute to an enhancement of the fundamental understanding of the electronic surface structure of GaRh alloys, which is crucially required for apprehending and thus further exploiting the improved catalytic activity of GaRh SCALMS.
CRIS-Team Scopus Importer:2023-11-17